2014
DOI: 10.1002/art.38232
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mortality Patterns Following Total Hip or Knee Arthroplasty Over the Past Two Decades: A Nationwide Cohort Study

Abstract: Objective. Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are effective procedures for patients with moderate-to-severe osteoarthritis. Mortality rates after THA and TKA may have changed because of new surgical techniques, improvement of peri-and postoperative care, and performance of surgery in older patients having multiple comorbidities. However, data on secular mortality trends are scarce. We undertook this study to evaluate mortality patterns between 1989 and 2007 in patients undergoing el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
(39 reference statements)
2
37
0
1
Order By: Relevance
“…We found decreasing mortality in the early post‐operative period (30 and 90 days) similar to other publications,29, 30 this despite an increase in comorbidity. The reason for this is likely to be multi‐factorial and will certainly include advances in in the pre‐ and peri‐operative investigation and care of patients.…”
Section: Discussionsupporting
confidence: 91%
“…We found decreasing mortality in the early post‐operative period (30 and 90 days) similar to other publications,29, 30 this despite an increase in comorbidity. The reason for this is likely to be multi‐factorial and will certainly include advances in in the pre‐ and peri‐operative investigation and care of patients.…”
Section: Discussionsupporting
confidence: 91%
“…With a mean follow-up of 11 years, we were able to show that the temporal improvements in in mortality is not just confined to the first year of surgery, and, at least in the case of total knee replacement, may have occurred even faster than the general population. Combined with the results of the short-term mortality studies[13, 14, 21], we can conclude that total hip and knee replacement patients have much lower mortality today than their counterparts about a decade ago.…”
Section: Discussionmentioning
confidence: 79%
“…Although this was previously demonstrated for short-term mortality[13, 14, 21, 22], only one prior study from Norway reported declines in long-term mortality[8]. In a nationwide total hip replacement cohort, investigators observed a statistically significant difference in the SMR between 1987–90 and 1995–98 but a significance test for trend was not significant.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have shown 30‐day mortality after hip and knee arthroplasty to be a little less than 0.5% and approximately doubling at 90 days. There is evidence that these rates have been decreasing over time . Early post‐operative mortality rates are higher than the expected mortality without surgery, based on population norms .…”
Section: Introductionmentioning
confidence: 99%